Iatrogenic Extrusion of Calcium Silicate Cements on Teeth Associated with Large Periapical Lesion: A Case Report with 12-Month Follow-up - Jawami, Afiq Azizi; Soo, Eason (UI Scholars Hub, 2022)
Traumatic dental injuries can result in pulp necrosis and apical periodontitis, impairing root development. When this condition is left untreated, it causes inflammation in the tissues at the apex, which may lead to significant damage of the periapical alveolar bone. Tooth with open apex may have a risk of iatrogenic error of extrusion material during the stage of root canal obturation. Objective: This case report discussed the bone healing of large periapical lesion of an iatrogenic extrusion of calcium silicate cement in an open apex maxillary left central incisor. Case report: A 35-year-old female patient presented with a main complaint of a discoloured upper front tooth that was affecting with her appearance. Clinical examination showed her left maxillary central incisor was diagnosed with pulp necrosis and symptomatic apical periodontitis. Periapical radiograph revealed the tooth has an open apex and large periapical lesion. After chemomechanical disinfection, an apical plug was placed with bioceramic material. Periapical radiographs taken postoperatively demonstrated the extrusion of bioceramic material into the periapical lesion. After a year, the tooth does not exhibit any symptoms, and periapical radiographs showed that the periapical region has totally healed. Conclusion: Extruded bioceramic material has no detrimental impact on periapical tissue healing, as evidenced by 12-month follow-up observations.